2010
DOI: 10.3109/13816810903584989
|View full text |Cite
|
Sign up to set email alerts
|

Novel IntragenicFRMD7Deletion in a Pedigree with Congenital X-Linked Nystagmus

Abstract: A range of missense, nonsense, frameshift, and splicing mutations in FRMD7 have been shown to cause X-linked congenital nystagmus. Here we show for the first time that large intragenic deletions of FRMD7 can also cause this form of nystagmus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Mutations of FRMD7 are the major etiological contributor of ICN (1)(2)(3)(4)(5). A previous study by the current authors demonstrated that FRMD7 interacts with RhoGDI, whereby it specifically activates the Rac1 signalling involved in neuronal development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations of FRMD7 are the major etiological contributor of ICN (1)(2)(3)(4)(5). A previous study by the current authors demonstrated that FRMD7 interacts with RhoGDI, whereby it specifically activates the Rac1 signalling involved in neuronal development.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no effective treatments for ICN and patients experience a significant decrease in their quality of life over time. To date, >40 mutations of FRMD7 have been detected worldwide in people from various ethnic backgrounds (1)(2)(3)(4)(5)(7)(8)(9). A previous study by the current authors identified two novel missense mutations (c.781C>G and c.886G>C) and a truncated mutation (c.1003C>T) of human FRMD7 in three X-linked ICN pedigrees (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 To date, 44 FRMD7 gene mutations have been identified in various NYS families suggesting that this gene has an important role in the NYS development. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The majority of these mutations were clustered in the highly conserved FERM-C domain in exons of 7-9 ( Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…[345678] Mutations in FRMD7 gene are the major causes of Chinese familial X-linked CN and account for approximately 47% of Chinese patients with the disorder. [9]…”
mentioning
confidence: 99%